Knowledge and Perception of Electronic Health Record among Nurses - Saima Riaz, Samina Nazir, Tabassam Zia, Tahira Yasmeen, Sadia Shoukat, Waqas Latif, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Proper Nursing documentation covers all aspects of health care such as assessment standards, proper diagnosis, and identification of problems, planning and implementation of interventions. Aim: To assess the Nurses’ Knowledge and Perceptions regarding Electronic Documentation. Study Design: Descriptive cross sectional study. Methodology: The study was conducted at Institute of Nursing University of Health Sciences Lahore Pakistan whereas the data was collected at four tertiary care Hospitals of Lahore. A Non-probability convenient sampling was used. A sample of n=310 nurses was recruited for this study. A self-administered questionnaire was filled by each participant in about 30minutes. The questionnaire included three parts such as demographic data, Knowledge questions and Perception questions. The collected data was analyzed by using SPSS version 26. Chi square ware applied with P-value< 0.05 as significant. Results: It was found that 26.45% of the study participants had poor knowledge regarding the electronic documentations who scored less than 50% of the correct responses. 32.58% of the nurses have average knowledge and they answered 50 to 65% correct questions. 37.74% participants’ nurses answered 65-80% correct and have good knowledge regarding the electronic documentation. It was also found that 78.71% of the nurses had positive perceptions regarding electronic documentation. Conclusion: It was concluded that there was lack of proper knowledge level but the perceptions toward the electronic documentation was positive among the participant nurses.